Nailing Jelly: The Replication Problem Seems to Be Unsurmountable. Two Failed Replications of the Matrix Experiment - Walach, Harald; Kirmse, Karolina A.; Sedlmeier, Peter; Vogt, Hans; Hinterberger, Thilo; von Lucadou, Walter (Journal of Scientific Exploration, 2022)
We have reported previously on positive effects found in the matrix experiment. This is a setup where a random event generator (REG) drives a display, which participants are instructed to “influence” at will, i.e., in a psychokinesis (PK) setup. The difference of this matrix experiment from standard micro-PK REG experiments was that the deviation from randomness was not measured, but a large array of 2025 correlations between the behavior of the participant and the behavior of the REG was tested. This previous experiment was significant, and we devised a consensus protocol, which was deposited before commencement, according to which we conducted two independent replications with the same experimental setup and equipment. In the first experiment 64 participants conducted the experiment in one location under the experimental guidance of KK, in the second experiment 40 participants conducted the experiment in another location under the experimental guidance of HV. The analysis used a non-parametric randomization test with 10,000 iterations. None of the two experiments was significant. While in the first experiment a very small, but non-significant effect was found, in the second experiment no effect whatsoever was detectable. Sensitivity analyses did not suggest that the effect was in fact there but overlooked by our analysis. We discuss the findings in the context of the larger debate around replicability of parapsychological (PSI) research results and our theoretical model. This starts from the assumptions that such PSI effects are likely effects of a generalized form of entanglement correlations, and a consequence of this model is that such effects must not be used for the transfer of signals. Classical experiments, however, are detectors or extractors of signals in or from systems. This seems to be prohibited. Thus, the replication problem and this failed replication is likely part of the systematic nature of these effects. This makes it unlikely that experimental research alone will be successful in the long run demonstrating PSI effects. Our conclusion is that the matrix experiment is not a replicable paradigm in PSI research.